Methylation status of CpG sites in the NOTCH4 promoter region regulates NOTCH4 expression in patients with tetralogy of Fallot - Zhu, Yanjie (Mol Med Rep, 2020)
Tetralogy of Fallot (TOF) is the most common form of cyanotic congenital heart disease (CHD). Although a lower methylation level of whole genome has been demonstrated in TOF patients, little is known regarding the DNA methylation changes in specific gene and its associations with TOF development. NOTCH4 is a mediator of the Notch signalling pathway that plays an important role in normal cardiac development. However, the role of epigenetic regulation of the NOTCH4 gene in the pathogenesis of TOF remains unclear. Considering the NOTCH4 low mutation frequency and reduced expression in the TOF patients, we hypothesized that abnormal DNA methylation change of NOTCH4 gene may influence its expression and responsible for TOF development. In this study, we measured the promoter methylation status of NOTCH4 and was measured and its regulation mechanism was explored, which may be related to TOF disease. Additionally, the promoter methylation statuses of NOTCH4 was measured in order to further understand epigenetic mechanisms that may serve a role in the development of TOF. Immunohistochemical analysis was used to examine NOTCH4 expression in right ventricular outflow tract myocardial tissues in patients with TOF. Compared with healthy controls, patients with TOF displayed significantly reduced in NOTCH4 expression (P=0.0055). Moreover, bisulphite sequencing suggested that the methylation levels of CpG site 2 in the NOTCH4 promoter was significantly higher in the patients than in the controls (P=0.0459). NOTCH4 expression was negatively associated with CpG site 2 methylation levels (r=−0.51; P=0.01). ETS1 transcription factor can serve as transcriptional activators by binding to specific DNA sequences of target genes, such as DLL4 and NOTCH4, which serves an important role in normal heart development. Dual-luciferase reporter and electrophoretic mobility shift assays indicated that the ETS1 transcription factor could bind to the NOTCH4 promoter region. However, binding of ETS1 to the NOTCH4 promoter was abrogated by methylation at the putative ETS1 binding sites. These findings suggested that decreased NOTCH4 expression in patients with TOF may be associated with hypermethylation of CpG site 2 in the NOTCH4 promoter region, due to impaired binding of ETS1.